AB0746 EVALUATING TENDER AND SWOLLEN JOINTS FOR THE ASSESSMENT OF INFLAMMATORY PAIN IN PSORIATIC ARTHRITIS USING ULTRASOUND. (2nd June 2020) - Bosch, P.; Husic, R.; Anja, F.; Gretler, J.; Lackner, A.; Graninger, W.; Duftner, C.; Hermann, J.; Dejaco, C.
Abstract : Background: Tender and Swollen Joint Counts (TJC, SJC) are items of disease activity scores in rheumatoid arthritis (RA) and psoriatic arthritis (PsA). Recent studies suggest that TJC do not adequately reflect ongoing inflammation in RA when using Ultrasound (US) as a reference standard, and that pain might be due to other, non-inflammatory causes. 1, 2 In PsA, the role of tenderness and swelling of joints for reflecting active inflammation has not been well studied so far. Objectives: To evaluate tender (TJ) and swollen joints (SJ) for the assessment of inflammation in PsA. Methods: We performed a prospective study on 83 PsA patients undergoing clinical and ultrasound examinations at two study visits scheduled 12 months apart. Tenderness and swelling were assessed for 68 and 66 joints respectively and US examinations, including grey scale (GS) and power doppler (PD) were conducted at all 68 joints. GS- (range 0-204) und PD sum scores (0-204) were calculated. At patient level, correlations were performed between TJC, SJC and clinical or US values. At joint level a GS value≥1 and/or PD value≥1 was defined as active synovitis, which was compared to whether a joint was tender, swollen or both. A generalized linear mixed model was created to assess the predictive value of TJ and SJ for active synovitis after 12 months, taking into consideration the joint site. Results: At baseline the median TJC and SJC for 83 patients was 4 (range 0-59) and 1 (0-20), respectively and the median GSS- and PD sum score was 16 (3-56) and 3 (0-31) respectively. SJC correlated with the GSS sum score (r= 0.37, p=0.004) and PD sum score (r =0.47, p<0.001), while TJC only correlated with PD sum score (r=0.33, p=0.01). TJC correlated better than SJC with patient reported outcomes like patient global assessment (TJC: r=0.57, p<0.001; SJC r=0.39, p=0.002) and health assessment questionnaire (TJC: r=0.50, p<0.001, SJC no significant correlation). Swollen joints (with or without tenderness) showed active synovitis (GSS≥1 and/or PD≥1) in 67.6% of cases, while tender joints (with or without swelling) showed signs of US activation in only 34.5%. A joint that was considered swollen at baseline was more likely to express active synovitis after 12 months (OR: 4.3, 97.5 CI: 2.9-6.2), compared to a joint that was either tender or swollen at baseline (OR: 2.8, 97.5 CI: 2.1-3.5). Conclusion: SJC are more closely linked with US signs of inflammation as compared to TJC in PsA. While swelling of a joint predicts US inflammation after a year, the information whether the joint is additionally tender or not, gives no additional predictive information. References: [1]Hammer HB, Michelsen B, Sexton J, et al. Swollen, but not tender joints, are independently associated with ultrasound synovitis: results from a longitudinal observational study of patients with established rheumatoid arthritis. Ann Rheum Dis 2019;78:1179-85. [2]Hammer HB, Michelsen B, Provan SA, et al. Tender joint count may not reflect inflammatory activity in established rheumatoid arthritis patients - results from a longitudinal study. Arthritis Care Res (Hoboken ) 2018 Disclosure of Interests: None declared